2017
DOI: 10.1016/j.jcte.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy and its relationship with glomerular filtration rate and other risk factors in patients with type 2 diabetes mellitus in Spain. DM2 HOPE study

Abstract: HighlightsIn Spain, diabetic retinopathy (DR) prevalence in type 2 diabetic patients was 14.9%.DR was higher in women and older patients.eGFR, duration of disease, HbA1c ≥ 7% and high blood pressure were associated with DR.DR was also higher in patients taking insulin.Patients with DR used to have comorbidities more frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 26 publications
7
30
2
5
Order By: Relevance
“…This study identified that diabetic retinopathy was 51.3% prevalent among the enrolled type 2 diabetes patients. This finding is higher than the prevalence previously reported from Arbaminch [29] and Jimma [28] in Ethiopia and from other parts of the world [18][19][20][21][22][23][24]. However, our finding is lower than the one reported from Bahol in Iran [25].…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…This study identified that diabetic retinopathy was 51.3% prevalent among the enrolled type 2 diabetes patients. This finding is higher than the prevalence previously reported from Arbaminch [29] and Jimma [28] in Ethiopia and from other parts of the world [18][19][20][21][22][23][24]. However, our finding is lower than the one reported from Bahol in Iran [25].…”
Section: Discussioncontrasting
confidence: 92%
“…Similar with previous research findings reported from other settings [18,[20][21][22], our study revealed that the risk to have diabetic retinopathy among type 2 diabetes increases with the duration of the disease, higher HbA1c (>7%), and presence comorbid hypertension. Therefore, early diagnoses of diabetes and diabetic retinopathy, and continuous diabetes selfmanagement education can improve the control of these risk factors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the gender factors, Lopez et al (2017) determined that retinopathy in women are more common related to retinopathy in elderly patients with T2DM. 23 Another retrospective study also found that women were more likely to have retinopathy than men 24 , the results of which matched the results of this study. The estrogen production could regulate ocular blood flow to protect the retina; and its antioxidant effects were the primary protective effect on the lens.…”
Section: Discussionsupporting
confidence: 86%